A preliminary investigation of infopreneurship education for library, information and archives management students in Hebei, China / Ba Xi, Nurussobah Hussin and Hanis Diyana Kamarudin - Xi, Ba; Hussin, Nurussobah; Kamarudin, Hanis Diyana (Faculty of Information Management, 2023)
Infopreneurship education plays a pivotal role in imparting essential entrepreneurial skills and facilitating the growth and prosperity of informationbased enterprises. China's research on infopreneurship education has continuously developed. However, there are still many shortcomings, such as insufficient teachers, not reflecting the characteristics of the specialty, and poor implementation of the practice. This paper focuses on the significance, necessity, and shortcomings of infopreneurship education for library information and archive management majors in Hebei Province, China. This paper adopts the literature analysis and other parties to cooperate in promoting the practical development and theory construction of infopreneurship education in Hebei method, extensively searches Chinese and foreign literature databases, and analyzes the closely related Chinese and English literature. Finally, the paper points out that there is a need for the government, schools, society, enterprises, scholars, China